FEMALE VOTER PARTICIPATION IN THE 2024 GENERAL ELECTION OF BAUBAU CITY DPRD MEMBERS - Edi Sabara; Andi Tenri; La Didi (CV. RADJA PUBLIKA, 2025)
Research purposes For analyze participation voters Woman in General Election for Members of the Baubau City Regional People's Representative Council 2024. Problems​ study focused on gaps between height level participation numeric voters Woman with quality participation political in a way substantive , representative , and its influence to taking decision public . For answer problem said , research This use references theoretical from field administration public , participation politics , gender studies , and governance democracy . Data collected through interview in-depth , observation , and documentation with involving organizer elections , voters women , and members legislative women , then analyzed in a way qualitative use technique interactive data analysis . Research results show that mechanism administrative gender responsive elections , policies affirmative , and involvement meaningful Woman in institution organizer elections capable increase participation and trust Woman towards the democratic process . Although representation women in institutions legislative Still limited in a way quantitative , its existence give contribution substantive to policy more public​ inclusive and gender responsive . Research This conclude that strengthening commitment institutional , regulatory gender and culturally sensitive inclusive organization​ is key For overcome obstacle structural and cultural as well as speed up equality political women at the level local .